Opinion of Inflation and Methods of Protection Against its Negative Effects of Students - Buta, Bartosz (Journal of Finance and Financial Law, 2023)
The purpose of the article/hypothesis: The purpose of the article is to show and analyze the point of view and knowledge of students in terms of inflation and methods of protection against its negative effects. Methodology: The work consists of desk research of modern inflation and analysis of data gathered by questionnaire entitled “Opinion of inflation and methods of protection against its negative effects of students” containing both closed-ended and open-ended questions. The research was conducted using CAWI method on 329 respondents. The selection of the sample was random. Results of the research: Students are aware of current (at the time) inflation rate, although they do not know the exact interpretation of it. They apply some preventive methods to protect their savings such as paying attention to what they buy. There is still part of students who do not protect their savings against negative effects of inflation at this moment, but if inflation rate was higher, they would. Public bodies responsible of preventing price increases and mitigating the negative effects of inflation are not trusted by students. Even though students know destructive impact of inflation they are aware of its potential positive effects of economy when well managed and under control.